2016
DOI: 10.1186/s40175-016-0050-1
|View full text |Cite
|
Sign up to set email alerts
|

Wage inequality and informality: evidence from Mexico

Abstract: While several studies have documented the expansion of the informal sector and its detrimental impact on development, few have noted that informality and wage inequality tend to move together. Using Mexico as a case study, I show that between 1987 and 2002 wage inequality within informal workers accounted for over 60 % of total wage inequality and that the Mexican financial crisis of the mid-1990s increased the share of informal workers and, via this, wage inequality. The results provide supportive evidence th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 32 publications
(59 reference statements)
1
16
0
7
Order By: Relevance
“…An important aspect that relates to our study is that countries with high prevalence of informal markets tend to have higher levels of wage inequality and lower levels of economic development (Binelli, 2016). In Mexico, wage inequality within informal workers accounted for more than 60 percent of the overall wage inequality between 1987 and 2002 (Binelli, 2016). The 1995 Mexican financial crisis increased the share of informal workers and wage inequality, which affected the national economy and resulted in significant unemployment among formal employees.…”
Section: Informal Economic Sector In Developing Countriesmentioning
confidence: 91%
See 3 more Smart Citations
“…An important aspect that relates to our study is that countries with high prevalence of informal markets tend to have higher levels of wage inequality and lower levels of economic development (Binelli, 2016). In Mexico, wage inequality within informal workers accounted for more than 60 percent of the overall wage inequality between 1987 and 2002 (Binelli, 2016). The 1995 Mexican financial crisis increased the share of informal workers and wage inequality, which affected the national economy and resulted in significant unemployment among formal employees.…”
Section: Informal Economic Sector In Developing Countriesmentioning
confidence: 91%
“…Increases in wage inequality are related to differences in inequality within formal and informal workers, relative to inequality between formal and informal workers. Results from instrumental variable regressions and decomposition exercises suggest increases in wage inequality with the rise in informal economic sector (Binelli, 2016).…”
Section: Informal Economic Sector In Developing Countriesmentioning
confidence: 98%
See 2 more Smart Citations
“…More recently, Binelli (2016) contributed to the literature by studying the case of Mexico from 1987-2002. When considering salaried employees, she found that wage inequality for informal workers accounts for 60% of the total wage inequality.…”
Section: Literature Reviewmentioning
confidence: 99%